2019
DOI: 10.1080/10942912.2019.1622564
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of polyphenol-rich pomegranate peel extract against Cronobacter sakazakii

Abstract: The purpose of the study was to determine if pomegranate (Punica granatum L.) peel contains polyphenolic compounds with antibacterial activity against Cronobacter sakazakii. Minimum inhibitory and bactericidal concentrations of a methanolic extract were found to increase significantly (P < .05) with decreasing temperature (37, 21, 10°C) and pH (6.0, 5.0, 4.0). Chemical analysis by high pressure liquid chromatography revealed that the elligitannins αand β-punicalagin were most abundant hydrolysable polyphenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…% (Figure 4). These results are clearly indicative of the high antimicrobial performance of pomegranate seed and peel extracts, as reported by several authors [57,58]. This behaviour can be related to the polyphenolic compounds present in PSP in accordance with previous results linking the antibacterial activity of pomegranate fruit and peel extracts with their total polyphenols content [59][60][61], being phenols, tannins and flavonoids the major active compounds responsible for this activity.…”
Section: Antimicrobial Activity Of Fg/psp Filmssupporting
confidence: 91%
“…% (Figure 4). These results are clearly indicative of the high antimicrobial performance of pomegranate seed and peel extracts, as reported by several authors [57,58]. This behaviour can be related to the polyphenolic compounds present in PSP in accordance with previous results linking the antibacterial activity of pomegranate fruit and peel extracts with their total polyphenols content [59][60][61], being phenols, tannins and flavonoids the major active compounds responsible for this activity.…”
Section: Antimicrobial Activity Of Fg/psp Filmssupporting
confidence: 91%
“…Among these, plant crude extracts were more suitable as the natural disinfectants due to their low cost and simple processing technique. Yemis et al (2019) found that the MIC of polyphenol-rich pomegranate peel extract against C. sakazakii was 20 mg/mL. Fei et al (2020) explored the possibility of Amaranthus tricolor crude extract (ATCE) as a potential disinfectant and found that the MIC and MBC of ATCE against C. sakazakii were 20 and 40 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC of ATCE against C. sakazakii strains was 20 mg/mL, a value higher than that of some other pure natural products, such as eugenol (MIC = 1.0 mg/mL), lipoic acid (MIC = 2.5-5 mg/mL), and syringic acid (MIC = 5.0 mg/mL) (Bajpai et al, 2013;Shi et al, 2016b,c), which indicated that further concentrations of ATCE should be evaluated to achieve a better bacteriostatic effect. Similarly, the average MIC of polyphenol-rich pomegranate peel extract (pH = 6.0) against C. sakazakii was 20 mg/mL, according to the report of Yemis et al (2019), who deemed that a MIC of 20 mg/mL was acceptable for the crude extract, and that a concentration process be performed before using the extract as a disinfectant.…”
Section: Discussionmentioning
confidence: 99%